Net-Zero Carbon Event to Support Sustainable Tourism in Indonesia - Riyanthi Handayani; Agus Riyadi; Sri Mariati (Jurnal Penelitian Pariwisata, 2026)
This study aims to analyze the implementation of Net Zero Carbon Events (NZCE) principles at the Bali Nusa Dua Convention Center (BNDCC) and the Jakarta Convention Center (JCC) in supporting sustainable tourism. The study uses a mixed-methods approach. It combines qualitative interviews and participant observation with quantitative SWOT and IE matrix analysis. The results show that both venues have strengths in green infrastructure and renewable energy. However, they face challenges such as budget constraints and limited coordination between departments. External opportunities, including government support and technological innovation, can be leveraged to improve NZCE implementation. The findings suggest strategies such as diversification, stronger stakeholder collaboration, and enhanced human resource capacity. These strategies are important to support environmentally friendly and sustainable MICE events in Indonesia. Keywords: Net Zero Carbon Events (NZCE), MICE, Sustainable Tourism, Green Infrastructure, SWOT Analysis, management event, carbon neutrality